Structure and bonding in [Sb@In8Sb12]3− and [Sb@In8Sb12]5− - Liu, C; Tkachenko, NV; Popov, IA; Fedik, N; Min, X; Xu, C-Q; Li, J; McGrady, JE; Boldyrev, AI; Sun, Z-M (Wiley, 2019)
We report the characterization of the compound [K([2.2.2]crypt)]4 [In8 Sb13 ], which proves to contain a 1:1 mixture of [Sb@In8 Sb12 ]3- and [Sb@In8 Sb12 ]5- . The tri-anion displays perfect Th symmetry, the first completely inorganic molecule to do so, and contains eight equivalent In3+ centers in a cube. The gas-phase potential energy surface of the penta-anion has eight equivalent minima where the extra pair of electrons is localized on one In+ center, and these minima are linked by low-lying transition states where the electron pair is delocalized over two adjacent centers. The best fit to the electron density is obtained from a model where the structure of the 5- cluster lies close to the gas-phase transition state.